Breakage of infant milk formula through three different processing methods and its influence on powder properties. (October 2020) - Han, Jie; Fitzpatrick, John; Cronin, Kevin; Maidannyk, Valentyn; Miao, Song
Abstract: Dairy powder breakage has always occurred during production and transportation though few studies on it have been published. This paper examines the breakage of infant formula using three different processing methods (laboratory high-speed mixing, lab-scale pneumatic conveying, and factory-scale blending) and the effect of breakage on powder properties. In both mixing and high-velocity pneumatic conveying, particles were broken into smaller entities and the particle size of samples significantly decreased. Particle breakage was accompanied by a significant decrease in porosity and increase in density and surface free fat. This in-turn decreased the rehydration properties of samples, especially for high-speed mixing, while breakage had only a small influence on powder flowability. By contrast, some agglomeration occurred during blending for short time in the blender and the particle size did not decrease ( P >  0.05) even for blending at longer time, thus, there were only minor impacts on physical and functional properties of powders. Highlights: High-speed mixing and pneumatic conveying caused significant breakage of agglomerated infant formula. Powder breakage caused increased bulk density and surface free fat. Powder breakage decreased the rehydration properties of powders, but had only a small influence on powder flowability. Factory-scale blending had little influence on physical properties of agglomerated infant formula.